Tandem CAR-T cell therapy: recent advances and current challenges - Sara Gómez-Melero; Sara Gómez-Melero; Fakhri Hassouneh; Isabel M. Vallejo-Bermúdez; Eduardo Agüera-Morales; Eduardo Agüera-Morales; Rafael Solana; Javier Caballero-Villarraso; Javier Caballero-Villarraso; Javier Caballero-Villarraso (Frontiers in Immunology)
CAR-T cell therapy has revolutionized cancer treatment. However, despite the achievements of this approach, there are still clinical challenges to address, such as antigen loss and the design of an optimal CAR structure. Multi-targeted CAR-T therapies, including tandem CAR-T cells, have emerged as a strategy to overcome some of these limitations and improve outcomes. Tandem CAR-T cells are currently being evaluated in preclinical and clinical studies for the treatment of hematological malignancies and solid tumors, showing promising results. These CARs have demonstrated efficacy, safety, and a relatively low relapse rate in these studies. Research suggests that TanCAR-T cells can enhance the outcomes and benefits of CAR-T cell therapy. However, challenges such as identifying the ideal CAR construct, selecting appropriate targets, and improving transduction efficiency remain unresolved, and further research is essential to address these limitations. This review highlights the potential of tandem CAR-T cells as a cancer treatment, summarizing preclinical and clinical studies with this innovative therapy and emphasizing the importance of continued research to overcome its limitations and improve its effectiveness.